Korespondencja (1954)
Listy od następujących, Wil.-Win.:
a 1978 601
Keywords: Bydgoszcz; m., Państwowe Teatry Ziemi Pomorskiej, Scena Bydgoska (Winter); m., Państwowy Teatr Polski (Winnicka); Kalisz; m., Państwowy Teatr im. W. Bogusławskiego (Winkler); Teatr polski 20 w.; Teatr polski zob. też dramaty, opera, programy, recenzje